Selected socio-economic factors affecting the willingness to minimise solid waste in Dhaka city, Bangladesh - Rafia, Afroz; Tudin, Rabaah; Hanaki, Keisuke; Masud, Muhammad Mehdi (Routledge, 2011)
This paper examines the factors that influence the waste generation and willingness to minimise solid waste in Dhaka city, Bangladesh. Information on waste generation, willingness to minimise, socio-economic characteristics, and behaviour of the households towards solid waste management were obtained from interviews with 402 households in Dhaka city. Of these, 103 households regularly practised recycling activities. Ordinary least square (OLS) regression and logistic regression analysis were used to determine the dominant factors that might influence the waste generation and households’ willingness to minimise solid waste, respectively. The results found that the waste generation of the households in Dhaka city was significantly affected by environmental consciousness, income groups, particularly the middle-income earners, and willingness to separate. The significant factors for willingness to minimise solid waste were environmental consciousness, income groups particularly the middle-income earners, young adults mainly those aged between 25 to 35 years and storage facility. Establishment of a solid waste management programme could be an effective strategy for implementing sustainable waste management in Bangladesh. For this strategy to succeed, however, active partnership between the respondents and waste management service department is required. The respondents’ behaviour toward solid waste management practices should be taken into consideration, as should the results of this study, which are important indicators of respondents’ positive attitudes toward sustainable waste management in Dhaka city.